ELM and inter-ELM tungsten erosion sources in high-power, JET ITER-like wall H-mode plasmas. (October 2022) - Kumpulainen, H.A.; Groth, M.; Brezinsek, S.; Corrigan, G.; Frassinetti, L.; Harting, D.; Koechl, F.; Karhunen, J.; Meigs, A.G.; O'Mullane, M.; Romazanov, J.; ,
Highlight: High-power type-I ELMy JET plasmas simulated using JINTRAC and ERO2.0. Near-perfect screening predicted for highest gross W sources at divertor targets. W influx to main plasma mostly from LFS divertor entrance due to erosion by CX atoms. Predicted W I emission consistent with measurements in the LFS divertor. W II emission underpredicted by a factor of 10; potential reasons identified. Abstract: Simulations of JET ITER-like wall high-confinement mode plasmas, including type-I edge-localised modes (ELMs), using JINTRAC for the background plasmas and ERO2.0 for tungsten erosion and transport, predict virtually perfect screening of the primary W erosion sources at the divertor targets during both the ELM and inter-ELM phases. The largest source of W influx to the main plasma is predicted to be the outer vertical divertor due to sputtering by energetic fuel (D, T) atoms from charge-exchange reactions. ERO2.0 predictions accurately reproduce the measured W I emission in the low-field side divertor, but underpredict the W II emission by a factor of 10. Potential reasons for the W II discrepancy include uncertainties in the atomic data, assumptions on the sheath properties and the sputtering angle distribution, and the impact of metastable states.